DEVELOPMENT OF WORK SHEET OF STMIK ASIA MALANG STUDENTS IN THE OPERATION RESEARCH MATERIALS WITH THE STAD TYPE COOPERATIVE APPROACH - Puji Subekti; Fadhli Almu'iini Ahda (FMIPA UNIVERSITAS NEGERI MALANG, 2019)
Operation Reserach is a compulsory subject that must be taken by Informatics Engineering students at STMIK Asia Malang. This course has many benefits especially in making student final assignment programs. students need to practice a lot of questions to build a system that will be made in programming. This course can be an alternative to making decision-making systems with the methods needed. However, there are not a few students who are irregular in practicing practice questions. Student interest tends to be less because there are no different motivations and nuances in practicing questions. In connection with these problems, it is necessary to conduct research on the development of worksheets for STIMIK Asia Malang students in operation research subjects with the STAD type cooperative approach with the aim of producing more regular worksheets for students and in accordance with the methods applied. The research model used in this study is to use the stad type cooperative approach. The STAD Cooperative Learning Model is one of the simplest types of cooperative learning where students are placed in a four-member learning team that is mixed according to their level of performance, gender and ethnicity. The lecturer presents the subject then the student works in the team to ensure that all team members have mastered the subject with student worksheets.